Évolution des images du FLE à l'université : une étude de cas au Portugal - Sílvia Melo-Pfeifer; Susana Pinto (Recherches en didactique des langues et des cultures)
Taking the concept of "image" as a central feature in the process of language teaching and learning, this article describes and attempts to understand the images of Portuguese higher education students concerning French as a foreign language, during two consecutive academic years. Our results show that these images are extremely academic and homogeneous at the two different moments of the research. This main conclusion allows us to reflect upon the role of the curriculum in the construction and evolution of those images and also upon the need to make higher education discourse more aware of plurilingualism.